Thermal stability of reconstituted milk protein concentrates: Effect of partial calcium depletion during membrane filtration. (December 2017) - Eshpari, H.; Jimenez-Flores, R.; Tong, P.S.; Corredig, M.
Abstract: Milk protein concentrate (MPC) powders are increasingly utilized in manufacturing of protein fortified beverages. Thermal stability of the protein dispersions is of significant importance in such applications. It is known that a decrease in pH can induce partial dissociation of casein micelles and modify the natural equilibrium of calcium and phosphate between the micelles and the serum phase. The presence of soluble casein may improve the rehydration properties of MPC powders, and may impact their thermal stability. The objective of this work was to investigate the effects of partial acidification of milk prior to ultrafiltration on the heat stability of reconstituted MPC dispersions. Milk protein concentrate powders were prepared from skim milk acidified to pH 6.0 by addition of glucono-δ-lactone, and then concentrated using ultrafiltration (UF) and diafiltration (DF). The heat stability of the reconstituted MPC dispersions was studied, by determining heat coagulation time, particle size, turbidity, viscosity, soluble and colloidal calcium and phosphate, and non-sedimentable casein both before and after heating at 120 °C. Reconstituted MPC powders made with partially acidified skim milk contained lower soluble calcium and phosphate and exhibited very poor thermal stability compared to MPC powders made with skim milk at its natural pH. The thermal stability of the acidified MPC dispersions was not only recovered by restoration of pH and the serum composition through dialysis against skim milk, but it was improved compared to control MPC dispersions. All dialyzed samples had comparable pH, protein content and calcium and phosphate concentration, but the structure of the casein micelles was altered, causing differences in the type of soluble aggregates. It was concluded that the integrity of the casein micelles and the amount of dissociated, non-sedimentable caseins play a major role in determining the thermal stability of the MPC dispersions. Graphical abstract: Highlights: Milk was ultrafiltered to a target pH of about 6.0, and different MPC powders obtained. All MPC powders showed less heat stability than skim milk control at the same protein concentration. Heat stability of reconstituted MPC decreased with preacidification. Heat stability of preacidified MPC improved if the original milk serum composition was reestablished. Treatment of MPC at 120 °C did not cause significant deposition of calcium and phosphate on the micelles.